A study of the effect of compaction on particle breakage of sub-base and base material used for pavement construction in Ghana - Arthur, Thomas David (2011)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of Master of Philosophy degree in Civil Engineering.